The Distribution of Public Services: An Exploration of Local Governmental Preferences - Behrman, Jere R.; Craig, Steven G. (American Economic Review, 1987)
A local governmental welfare function is specified to explore two of its central characteristics: the equity-productivity trade-off and differential weights across neighborhoods. The constrained maximization model is estimated using service outcomes (safety) in the welfare function, as opposed to publicly provided inputs (police), over neighborhoods. The equity-productivity trade-off is found to be considerable, and not all neighborhoods are weighted equally. The results show that inequality aversion and unequal concern by local government over service outcomes must be addressed explicitly to understand the observed distribution of publicly provided inputs, with important implications for standard analysis of local governmental behavior. Copyright 1987 by American Economic Association.